2017
DOI: 10.1007/s00011-017-1120-9
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin 1–7, but not the thrombin-cleaved osteopontin C-terminal fragment, attenuates osteopontin-mediated macrophage-induced endothelial-cell inflammation

Abstract: OPN-C induces lower macrophage-induced endothelial inflammation compared to OPN-FL or OPN-N, but unlike angiotensin 1-7, fails to prevent endothelial inflammation induced by subsequent pro-inflammatory macrophage stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Recent studies have found that the MMP-3 or 7 cleavage of OPN-C fragments results has aα9β1 binding site, which facilitates its role in the development of inflammatory arthritis [ 50 ]. Another study has shown that OPN-C promotes inflammation by the activation of the NF-κB pathway [ 51 ]. We found that OPN-WT and cleaved forms of OPN coexisted in the ipsilateral cortex following HI injury in neonatal mice, and the C-terminal domain of OPN was the molecular basis for the direct binding between OPN and GAL-3.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that the MMP-3 or 7 cleavage of OPN-C fragments results has aα9β1 binding site, which facilitates its role in the development of inflammatory arthritis [ 50 ]. Another study has shown that OPN-C promotes inflammation by the activation of the NF-κB pathway [ 51 ]. We found that OPN-WT and cleaved forms of OPN coexisted in the ipsilateral cortex following HI injury in neonatal mice, and the C-terminal domain of OPN was the molecular basis for the direct binding between OPN and GAL-3.…”
Section: Discussionmentioning
confidence: 99%
“…The macrophages which were recruited to the site of injury released a variety of proinflammatory cytokines such as interleukin-1 β (IL-1 β ) and tumor necrosis factor α (TNF- α ) [16], which had the functions of removing cell debris and apoptotic bodies [1], phagocytizing necrotic substances, releasing CCL2, CX3CL1, and other chemokines [17], and promoting muscle healing [18] and immune cell infiltration [19]. Stimulation of macrophages could induce endothelial cell inflammatory response [20].…”
Section: Discussionmentioning
confidence: 99%
“…This sequence is disrupted following thrombin cleavage, but the loss of the pro-chemotactic activity in intact OPN is compensated for by the released OPN-CTF, which acquires a new conformation-dependent chemotactic activity towards DC [ 194 ]. Activity of OPN-CTF was confirmed in a human macrophage cell line (U937) where OPN-CTF was not as pro-inflammatory as OPN-FL and OPN-R [ 195 ]. Thus, thrombin cleavage of OPN occurs in vivo, and proteolysis regulates the functions of OPN with both generated fragments, OPN-R and OPN-CTF, acquiring different properties than possessed by OPN-FL.…”
Section: Protease Cleavages Of Opnmentioning
confidence: 99%